Forecasting volatility in Nordic stock markets : Evaluation of GARCH model performance in tail risk forecasting - Nurmi, Matti (My University, 2023)
For the past few years, stock markets have seen increased turbulence, first due to the Covid pandemic and second due to the war in Ukraine. This elevated risk regime, as well as rapid and substantial changes in stock prices, have highlighted the importance of proper risk management and forecasting tools. Hence, improving volatility forecasts allows market practitioners to assess risk exposure more accurately, and as different banks and financial institutions have been reported struggling due to changed market conditions, this topic has become more relevant. This thesis analyses the performance of different GARCH models in Value-at-Risk and Expected Shortfall estimation under three distributional assumptions in Nordic stock markets. The data consists of the daily closing of OMXHPI (Finland), OMXSPI (Sweden), OMXCPI (Denmark), and OSEAX (Norway) indices for the period 1.1.2012–31.12.2021. The data is further divided into three sample periods that reflect prevailing market conditions before and during the Covid pandemic, for which the forecasts are made. The GARCH models are first examined with in-sample tests, after which out-of-sample performance is analysed by backtesting the Value-at-Risk and Expected Shortfall forecasts. Moreover, forecasts made with historical simulation are used as a benchmark for the forecasts made with GARCH models. The results provided by this thesis confirm that GARCH models can make adequate forecasts during turbulent market periods, but the forecasting accuracy significantly decreases after the markets react to the Covid pandemic. However, when the period of increased volatility is prolonged, the models adapt to the elevated risk rather well, and the trend of model performance is similar within each market. Additionally, the in-sample analysis indicates that less complex models are able to capture return characteristics better than the more complex ones. Furthermore, the results for each market confirm that the forecasting accuracy can be increased more significantly by changing the distributional assumptions for the returns rather than changing the conditional volatility model.

Osakemarkkinoilla on viime vuosien aikana nähty lisääntynyttä epävarmuutta ensinnäkin Covid-pandemian ja toiseksi Ukrainan sodan vuoksi. Kohonnut riskitaso sekä nopeat ja merkittävät muutokset osakkeiden hinnoissa ovat korostaneet asianmukaisten riskienhallinta- ja enustamistyökalujen tärkeyttä. Näin ollen volatiliteettiennusteiden parantaminen antaa markkinoiden toimijoille mahdollisuuden arvioida riskialttiutta tarkemmin, ja koska eri pankkien ja rahoituslaitosten on raportoitu kohdanneen vaikeuksia muuttuneesta markkinaympäristöstä johtuen, tästä aiheesta on tullut ajankohtainen. Tässä opinnäytetyössä analysoidaan eri GARCH-mallien suorituskykyä Value-at-Risk- ja Expected Shortfall -ennusteissa kolmen jakaumaoletuksen mukaisesti pohjoismaisilla osakemarkkinoilla. Tiedot koostuvat OMXHPI (Suomi), OMXSPI (Ruotsi), OMXCPI (Tanska) ja OSEAX (Norja) indeksien päätöskursseista ajanjaksolta 1.1.2012–31.12.2021. Tiedot jaetaan edelleen kolmeen otosjaksoon, joille ennusteet tehdään ja jotka kuvastavat vallitsevia markkinaolosuhteita ennen Covid-pandemiaa ja sen aikana. GARCH-malleja sopivuutta dataan tarkastellaan ensin arvioimalla mallien in-sample testien tuloksia. Tämän jälkeen Value-at-Risk ja Expected Shortfall ennusteiden tarkkuutta ja mallien suorituskykyä kolmelle otosjaksolle analysoidaan toteumatesteillä. Lisäksi historiallisilla simulaatioilla tehtyjä ennusteita käytetään vertailukohtana GARCH-malleilla tehdyille ennusteille. Tämän opinnäytetyön tulokset vahvistavat, että GARCH-malleilla voidaan tehdä melko tarkkoja ennusteita epävarmalla markkinajaksolla, mutta ennusteiden tarkkuus heikkenee merkittävästi Covid-pandemian aiheuttaman volatiliteetin kasvun jälkeen. Kuitenkin, kun korkean volatiliteetin jakso pitkittyy, mallit sopeutuvat kohonneeseen riskiin melko hyvin ja mallien suorituskyvyn trendi säilyy samanlaisen eri markkinoilla. Lisäksi in-sample testit osoittavat, että vähemmän monimutkaiset mallit pystyvät mallintamaan tuottosarjojen ominaisuuksia paremmin kuin monimutkaisemmat mallit. Lisäksi kunkin markkinan tulokset vahvistavat, että ennusteen tarkkuutta voidaan parantaa merkittävästi muuttamalla tuottojen jakaumaoletuksia GARCH-mallien sijaan.
Keywords: Value-at-Risk, Expected Shortfall, GARCH, EGARCH, FIGARCH, forecasting